2001
DOI: 10.1006/viro.2001.1134
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Human Endogenous Retroviruses-K LTRs Retain Transcriptional Activity in Vivo, the Mode of Which Is Different in Different Cell Types

Abstract: Solitary long terminal repeats (LTRs) of human endogenous retroviruses (HERVs), tens of thousands of which are spread all over the genome, contain a variety of potential transcription regulatory elements. Information on transcriptional behavior of individual solitary LTRs, however, is limited. We studied the transcriptional activity of several individual HERV-K LTRs in a variety of tissues and cell lines. The RT-PCR technique targeted at specific amplification of the U3 or U5 regions of individual LTRs togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Characterization of promoter activities of HERV-K, HERV-H, HERV-E, ERV9, and HERV-W families, the most intensively studied HERVs, revealed specific cell type preferences for each HERV family, and even individual elements of one family showed significant variation in transcription pattern (1,7,21,23,64,70,80). In some cases, transcription factor binding sites that interact with cell type-specific nuclear factors could be identified, demonstrating that the expression of HERVs is regulated in a complex and diverse manner comparable to cellular genes (19,34,35,40,54,70; for a review, see reference 42).…”
mentioning
confidence: 99%
“…Characterization of promoter activities of HERV-K, HERV-H, HERV-E, ERV9, and HERV-W families, the most intensively studied HERVs, revealed specific cell type preferences for each HERV family, and even individual elements of one family showed significant variation in transcription pattern (1,7,21,23,64,70,80). In some cases, transcription factor binding sites that interact with cell type-specific nuclear factors could be identified, demonstrating that the expression of HERVs is regulated in a complex and diverse manner comparable to cellular genes (19,34,35,40,54,70; for a review, see reference 42).…”
mentioning
confidence: 99%
“…Human-specific HERV-K (HML-2) LTRs share significant sequence identity and form a well-defined cluster (named the HS family) in a phylogenetic tree (9,35). The members of this family, who have retained their transcriptional activity (4,15,16,47), were found to be tissue-specifically methylated (23,24,28) and probably still keep some infectious potential (13,17,39,44). The HS family is thought to be the most biologically active retroviral family in human cells.…”
mentioning
confidence: 99%
“…Particular attention will be given to HERVs, due to their possible role in human physiology and diseases, as well as to murine ERVs, due to the importance of this species as research model, both inside and outside genetics. Schon et al (2001) and Vinogradova et al (2001) showed that HERV LTRs display specific transcription patterns according to cell types, whereas patterns were consistent among different cell lines derived from the same type of tissue. Moreover, cells associated in the same tissue may display significant differences; for instance HERV-R is highly expressed in human endothelial and vascular smooth muscle cells in vitro but not in fibroblasts (Katsumata et al, 1999).…”
mentioning
confidence: 99%